MOBILE LEARNING ENVIRONMENT SYSTEM: PENGEMBANGAN MEDIA ANDROID DARI PERSPEKTIF VALIDITAS - Bimo Aji Nugroho (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
Digitization changes many things. One of which must follow the changes in digitalization is learning media. The massive use of mobile devices and the internet opens opportunities for the development of mobile learning. This article will explain the direction of the development of mobile learning in the world of modern education, especially in learning media. Although mobile devices and the internet are already massive, there is still a lack of media based on mobile learning. This study aims to test the validity of the android learning medium. This research is a research development (RD) learning medium developed based on Android. The model used in this study uses Tessmer, and then the validity test is carried out based on Nieveen (1999). The subjects of this study were 3 media experts based on the feasibility aspects of content, appearance, and language. The instrument used in this test is to determine the validity of an assessment rubric instrument. First, the expert test revealed that the learning media is valid in three aspects: content feasibility, language feasibility, and visual display feasibility. Second, this research will be the basis for the development of further android learning media, so that it is suitable for use by students.